THE IMPACT AND CHALLENGES OF FINANCIAL CYBERSECURITY: SAFEGUARDING THE DIGITAL ECONOMY - Tursunov, O.O (Innovative Development in Educational Activities, 2023)
This article explores the impact and challenges of financial cybersecurity, emphasizing the need for robust measures to safeguard the digital economy. It highlights the far-reaching consequences of financial cybersecurity breaches, including financial losses, data breaches, disruption of services, and regulatory repercussions. The article identifies and addresses the key challenges faced by financial institutions, such as sophisticated cyberattacks, third-party risks, regulatory compliance, insider threats, and the need for enhanced authentication and encryption. The solutions proposed include strong cybersecurity infrastructure, employee education and awareness, regular risk assessments, collaboration and information sharing, enhanced authentication and encryption, incident response planning, and regulatory compliance. By implementing these solutions, financial institutions can mitigate cyber risks and protect themselves and their customers from evolving threats